2017
DOI: 10.1016/j.rmed.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of exercise training responses in COPD patients with and without Alpha-1 antitrypsin deficiency

Abstract: Independently of the genetic variant of AAT, COPD patients achieved the same training-related benefit in 6MWD. Augmentation therapy showed no effect on 6MWD adaptation during PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
10
0
3
Order By: Relevance
“…Three studies were RCT, [60][61][62] one study was an open-label extension of an RCT 46 and four studies were retrospective cohort studies. [66][67][68][69] The evidence profiles for each outcome can be found in Appendix S2 (Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies were RCT, [60][61][62] one study was an open-label extension of an RCT 46 and four studies were retrospective cohort studies. [66][67][68][69] The evidence profiles for each outcome can be found in Appendix S2 (Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference between AAT augmentation therapy group and control group in functional capacity change, measured as change in an incremental shuttle walk test in an RCT 60 and as change in 6-min walking distance (6MWD) in an observational study. 67 Mortality. None of the reviewed studies were powered to evaluate mortality as an outcome.…”
Section: Exacerbations/lung Infections/hospitalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing the effects of pulmonary rehabilitation in patients with AATD-related COPD and general COPD concluded that the benefits in terms of physical performance increase were similar in both groups of patients. 32 However, data on emphysema distribution, comorbidities, and individual pharmacological therapy were not available in the database used for this study and so it cannot be excluded that patient comorbidities, which can have profound effects on quality of life, may have influenced results. The effects of exercise on specific clinical outcomes in AATD are likely positive but require further investigation.…”
Section: Non-pharmacological Interventions In the Management Of Aatd-associated Lung Diseasementioning
confidence: 99%
“…Dadurch hat sie im frühen Stadium der Erkrankung das Potenzial, den Krankheitsverlauf positiv zu beeinflussen [1,7]. Dies gilt auch für Patienten mit einem Alpha-1-Antitrypsin-Mangel [8].…”
Section: Indikationen Und Evidenzunclassified